Etiology and Management of Acute Metabolic Acidosis: An Update - Igor Matyukhin (Kidney & Blood Pressure Research, 2020)
Background: The etiology of acute metabolic acidosis (aMA) is heterogeneous, and the consequences are potentially life-threatening. The aim of this article was to summarize the causes and management of aMA from a clinician’s perspective. Summary: We performed a systematic search on PubMed, applying the following search terms: “acute metabolic acidosis,” “lactic acidosis,” “metformin” AND “acidosis,” “unbalanced solutions” AND “acidosis,” “bicarbonate” AND “acidosis” AND “outcome,” “acute metabolic acidosis” AND “management,” and “acute metabolic acidosis” AND “renal replacement therapy (RRT)/dialysis.” The literature search did not consider diabetic ketoacidosis at all. Lactic acidosis evolves from various conditions, either with or without systemic hypoxia. The incidence of metformin-associated aMA is actually quite low. Unbalanced electrolyte preparations can induce hyperchloremic aMA. The latter potentially worsens kidney-related outcome parameters. Nevertheless, prospective and controlled data are missing at the moment. Recently, bicarbonate has been shown to improve clinically relevant endpoints in the critically ill, even if higher pH values (>7.3) are targeted. New therapeutics for aMA control are under development, since bicarbonate treatment can induce serious side effects. Key Messages: aMA is a frequent and potentially life-threatening complication of various conditions. Lactic acidosis might occur even in the absence of systemic hypoxia. The incidence of metformin-associated aMA is comparably low. Unbalanced electrolyte solutions induce hyperchloremic aMA, which most likely worsens the renal prognosis of critically ill patients. Bicarbonate, although potentially deleterious due to increased carbon dioxide production with subsequent intracellular acidosis, improves kidney-related endpoints in the critically ill.